Synthesis and Electrochemical Properties of Nanocrystalline Nickel Molybdate - Popovych, O.M.; Budzulyak, I.M.; Popovych, O.V.; Rachiy, B.I.; Ilnytskyi, R.V.; Yablon, L.S.; Morushko, O.V. (Physics and Chemistry of Solid State, 2021)
We have obtained nanocrystalline hydrate and alpha phase of nickel molybdate by a hydrothermal technique. On the basis of the obtained cyclic voltammetry data, we have evaluated the contribution of faradaic and non-faradaic processes to the total capacitance of molybdates under study. It was found that the specific capacitance of hydrate NiMoO4·H2O is 621 F/g at a scan rate of 1 mV / s and the specific capacitance of the α-NiMoO4 is 281 F/g. Cathodes for hybrid supercapacitors were formed on the basis of the obtained nickel molybdates. As a result of electrochemical studies, it was found that the specific capacitance of hybrid supercapacitor based on NiMoO4·H2O/C was 256 F/g at the current of 0.2 A/g, while the specific energy was 80 W h/kg and specific power – 304 W/kg and these results are higher below in the α-NiMoO4 /C-based hybrid supercapacitor.